Technopreneurial competency effects on technology-based Bangladeshi SME performances: A structural equation modelling - Zainudin, Awang; Abu Shams Mohammad, Mahmudul Hoque; Benzamir, Ahmed Siddiqui (2018)
There has not been much writings about the effects of technopreneurial competencies (TC) on technology-based SME performance improvement; hence, there has yet to be sufficient progress made to ascertain the effects of technopreneurial competencies on technology-based SME performance especially in the emerging countries. This study intends to explore the effects of technopreneurial competencies on Bangladeshi SME performance. To do so, a causal model and a structured survey were conducted for collecting the perceptions of 180 technopreneurs in Bangladesh. The data has been analyzed and hypothesis has been tested using IBM-SPSS-AMOS package 25.0. This study has adopted the resource based view (RBV) of competencies which claimed that technopreneurial competencies are valuable, and intangible resources can lead towards better SME performance. The study has found that TC plays an influential role in organizational capability, in which results has shown that technopreneurial competencies portfolio has positive effects on the technology-based Bangladeshi SME performance. This study has contributed to the existing body of knowledge in technopreneurial competencies, and performance of Bangladeshi SME businesses. This study has recommended that it is important for technology-based SMEs to develop technopreneurial competencies in order to obtain better performance.